The Archaeology of Plural and Changing Identities
XII, 272 p.
Keywords: "Questions of identity have plagued the field of archaeology since its earliest antiquarian origins. The ability to discover, recover, or uncover a past culture required the assumption of a direct relationship between its material remains and social identity. Artifacts and architectural features alike have been conceptualized as "signatures" or "representations" of specific cultures – from the "Beaker People" of the European Neolithic to the "Georgian" world view of eighteenth century Colonial America. Thus, archaeologists have employed an explicitly material focus in their examinations of identity. Yet, as people move through life they continually shift affiliation from one position to another, dependent on the wider contexts of their interactions. Different forms of material culture may be employed as affiliations shift, and the connotations of any given set of artifacts may change. In this volume the authors explore these overlapping spheres of social affiliation. Social actors belong to multiple identity groups at any moment in their life. It is possible to deploy one or many potential labels in describing the identities of such an actor. Two main axes exist upon which we can plot experiences of social belonging -- the synchronic and the diachronic. Identities can be understood as multiple during one moment (or the extended moment of brief interaction), over the span of a lifetime, or over a specific historical trajectory." - from the Introduction The international group of contributions each illuminate how the various identifiers of race, ethnicity, sexuality, age, class, gender, personhood, health, and/or religion are part of both material expressions of social affiliations, and transient experiences of identity. The Archaeology of Plural and Changing Identities: Beyond Identification will be of great interest to archaeologists, anthropologists, historians, curators and other social scientists interestedin the mutability of identification through material remains.